(untitled) (Olhar de Professor, 2024)
This article is an excerpt from a study that aimed to understand the literacy conceptions of literacy teachers in Acre, their pedagogical practices in response to children’s different learning levels, and the implications of such practices for student development. Regarding the methodology, the research included a literature review, the development of a questionnaire, which was applied to four teachers, and the conducting of semi-structured interview. As a means of supporting the study, we drew on the works of Smolka (2013), Goulart (2019), Oliveira (2005), and Soares (2020). The results revealed that the teachers understand that reading and writing involve constructing meaning through writing and that they also show concern for teaching literacy in a meaningful way, grounded in the children’s reality. Additionally, the data indicate that, at times, they use traditional methods, blending them with methodologies that align with proposals stemming from literacy studies. The interviewees take on the role of mediators and highlight productive groupings as a strategy to address diversity. However, working with differences remains a significant challenge.